By-products of the nut and peanut agro-industry as sources of phytochemicals suitable for the nutraceutical and food industries - Vázquez-Flores, Alma A. (Apple Academic Press, 2018)
https://www.crcpress.com/Plant-Food-By-Products-Industrial-Relevance-for-Food-Additives-and-Nutraceuticals/Ayala-Zavala-Gonzalez-Aguilar-Siddiqui/p/book/9781771886406